Comparisons of Tensile Strength of Bamboo Fiber and Glass Fibre Epoxy Composite: Enhancing the mechanical properties of bamboo fiber reinforced polymer composites (Journal of Advances and Scholarly Researches in Allied Education, 2019)
One of the first building materials used by mankind was Bamboo. In Asia, bamboo is very usual for scaffolding, bridges, housing and some additional temporary structure. In numerous exaggeratedly populated provinces of the tropics, particular bamboo supply which is the only appropriate material that has been adequately inexpensive as well as abundant to encounter the widespread need for reasonable housing. This research work comprises the physical and mechanical properties tests of Bamboo for its usage in structural need in construction Industries and Structural Design Area. Bamboo fiber reinforced by polymer composites consists of moderate mechanical properties but their properties could be hugely improved by integration of synthetic fibers or by the treatment of fiber in the alkali medium.